Pediatric autoimmune neuropsychiatric disorders after streptococcus infection - Maini, Baljeet (Medknow Publications & Media Pvt Ltd, 2012)
Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal infection (PANDAS) is a group of disorders recently recognized as a clinical entity. A case of PANDAS is described here, which remitted after 1 month of treatment. Recent Group A beta-hemolytic streptococcus infection should be considered in a child who presents with a sudden explosive onset of tics or obsessive compulsive symptoms.